2015
DOI: 10.1093/cvr/cvv197
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of adipose tissue mesenchymal cells conjugated with VEGF-releasing microcarriers promotes repair in murine myocardial infarction

Abstract: AT-MSCs conjugated with VEGF-releasing PAMs exert paracrine effects that may have therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 16 publications
(23 reference statements)
0
33
0
Order By: Relevance
“…ASCs are more easily isolated and can differentiate toward the osteogenic, chondrogenic, adipogenic, myogenic, neurogenic and angiogenic lineages [2732]. …”
Section: Discussionmentioning
confidence: 99%
“…ASCs are more easily isolated and can differentiate toward the osteogenic, chondrogenic, adipogenic, myogenic, neurogenic and angiogenic lineages [2732]. …”
Section: Discussionmentioning
confidence: 99%
“…The later phases may be critical for tissue repair and regeneration and a continuous slow release of a therapeutic peptide (e.g. 430 VEGF and CST) released by microspheres transporting cells on their 3D functionalized surface may be beneficial for tissue engineering strategies (Elçin et al, 2001;Madonna et al, 2015). However, this needs to be ascertained in vivo for CST, and it should be ascertained whether other conditions, such as fibronectin coating, may affect the release of the active peptide.…”
Section: Discussionmentioning
confidence: 99%
“…In this way the combined action of the bioactive protein and the biomimetic surface can favor the survival and engraftment of the transported cells after their transplantation in different pathological conditions (Delcroix et al, 2011;Karam et al, 2012;Musilli et al, 2012;Quittet 85 et al, 2015;Savi et al, 2015;Tatard et al, 2007). Recently, it has been shown that PAMs releasing vascular-endothelial-growth-factor (VEGF) and conveying MSCs (derived from the adipose tissue) may induce their proliferation, angiogenic differentiation, and a decrease in cell death in vitro Madonna et al, 2015). Moreover, in an in vivo mice model of post-ischemic myocardium these functionalized PAMs implanted in the infarcted 90 myocardium enhanced MSC engraftment and differentiation into vascular structures resulting in myocardial fractional shortening improvement (Madonna et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaetani et al reported that epicardial application of CPCs in a 3D-printed gelatin/hyaluronic acid patch supported the long-term cell engraftment, significantly reduced adverse remodeling and improved cardiac function [443]. At the same time, biomaterials can serve as carriers containing functional molecules that boost the regenrative capacity of SCs such as VEGF, bFGF, HGF, IGF-1 and TGF-β [444][445][446][447][448].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%